Innovation and Entrepreneurship: Powerful Tools for a Modern Knowledge-Based Economy - Al-Mubaraki, Hanadi (Springer, 2015)
In this book, Hanadi Mubarak, Ali Husain and Michael promote the concept of innovation incubators from a business-management perspective. The book provides a comprehensive roadmap for the development of new economies based on technology, as well as value added in technology transfer, innovation development and an entrepreneurial climate.